Content marketing in e-commerce platforms in the internet celebrity economy. Issue 3 (28th January 2020) - Geng, Ruibin; Wang, Shichao; Chen, Xi; Song, Danyang; Yu, Jie
Abstract : Purpose: With the popularity of social media and, recently, live streaming, internet celebrity endorsements have become a prevalent approach to content marketing for e-commerce sellers. Despite the widespread use of social media and online communities, empirical studies investigating the economic value of user-generated content (UGC) and marketer-generated content (MGC) still lag behind. The purpose of this paper is to contribute both theoretically and practically to capture both first-order effects and second-order effects of internet celebrity endorsements on marketing outcomes in an e-commerce context. Design/methodology/approach: This study conducts a cross-sectional regression to evaluate the economic value of internet celebrity endorsement, and a panel vector autoregressive model is adopted to examine the relationship between celebrities' and consumers' content marketing behaviors and e-commerce sales performance. The authors also adopt look-ahead propensity-score matching technique to correct for selection bias. Findings: The empirical results show that the content generation efforts of marketers and the interaction behaviors between marketers and consumers will significantly influence the e-commerce sales, which refers to the first-order effects of internet celebrity endorsement. Moreover, interactions within the fan community exert second-order effects of content marketing on sales performance. Originality/value: This paper provides new insights for e-commerce retailers to evaluate the economic values of internet celebrity endorsement, a new content marketing practice in e-commerce platform.